Penurunan Lead Time Manufacturing Dengan Pendekatan Lean Manufacturing Studi Kasus Di PT. MKM - Fatma, Nur Fadilah; Ponda, Henri; Solehah, Solehah (Journal Industrial Manufacturing, 2023)
In the industrial world, it is very important to pay attention to the efficiency of production capacity where the manufacturing lead time for making shoe outsole is influenced by activities that are not value-added (Non Value Added) and activities that are not value-added but necessary (Necessary Non Value Added) in which there is some extravagance that occurs. These activities are in the form of temporary storage in the cooling room and the process of reworking defective products. The method used is Lean Manufacturing, the tools used are Value Stream Mapping (VSM) and Process Activity Mapping (PAM). VSM is used to identify activities that have cycle times exceeding takt time, followed by mapping the Activity Mapping process to analyze activities that are not Value Added. Based on the results of research from 4110 seconds, the process lead time of 3600 seconds is a non-value added activity. The rework process  and material storage in the cooling room were identified as having the largest value contributing to lead time, so rework must be eliminated. the percentage  of Process Cycle Efficiency (PCE) has increased. The reduction of the finished sheet material process is cooled to  the cooling room and the rework process  can save about 60 minutes of working time. Saving working hours can increase outsole production capacity  so that productivity increases and targets are achieved.Keywords: Lead Time Manufacture, Lean Manufacturing, Value Stream Mapping, Prose Activity Mapping. Process Cycle Activity.